Predicting the DRAM mZDI Using the PROMIS Anxiety and Depression. Issue 3 (1st February 2015) - Hung, Man; Stuart, Ami; Cheng, Christine; Hon, Shirley D.; Spiker, Ryan; Lawrence, Brandon; Neese, Ashley; Brodke, Darrel S.
Abstract : Study Design: Data were collected at a university orthopedic clinic in 2012. The final sample consisted of 316 patients. Sample included new and annual follow-up adult patients for all operative and nonoperative spine care. Outcome measures consisted of the patient-reported outcome measurement information system (PROMIS) anxiety 4-item short form (SF-4), the PROMIS depression SF-4, and the distress and risk assessment method modified Zung Depression Index (mZDI). Objective: The objective of this study was to assess whether the PROMIS anxiety 4-item short form (anxiety SF-4) or the PROMIS depression SF-4 (depression SF-4) can be used in place of the distress and risk assessment method mZDI. Summary of Background Data: Studies comparing the PROMIS short forms with the existing instruments are limited. In particular, there is not any published study comparing the PROMIS anxiety and depression short forms with the distress and risk assessment method mZDI. Methods: Regression analyses were carried out to predict the mZDI total scores from the PROMIS anxiety SF-4 T scores and the PROMIS depression SF-4 T scores. Intraclass correlation coefficients were computed on the actual and predicted mZDI scores. Results: All 3 instruments were highly correlated with each other. The PROMIS anxiety SF-4 and the PROMIS depression SF-4 were both able to explain a significant amount of variance in the mZDI. The intraclass correlation coefficients for the actual and predicted mZDI scores were high. The actual mZDI scores and predicted mZDI scores using either the PROMIS anxiety SF-4 or the PROMIS depression SF-4 across age and sex were similar. Conclusion: This study indicates that the PROMIS anxiety SF-4 scores and the depression SF-4 scores can accurately predict the mZDI scores. The PROMIS anxiety and depression short forms can be used as surrogates for the mZDI. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.This study examined whether the patient-reported outcome measurement information system anxiety or depression 4-item short forms can be used in place of the distress and risk assessment method modified Zung Depression Index. Results indicated that the patient-reported outcome measurement information system anxiety and depression scores can accurately predict the modified Zung Depression Index scores. The patient-reported outcome measurement information system anxiety and depression can be used as surrogates for the modified Zung Depression Index.